2021
DOI: 10.1021/acs.jnatprod.0c01369
|View full text |Cite
|
Sign up to set email alerts
|

Disproof of the Proposed Structures of Bradyoxetin, a Putative Bradyrhizobium japonicum Signaling Molecule, and HMCP, a Putative Ralstonia solanacearum Quorum-Sensing Molecule

Abstract: First, we revisited the reported NMR data of bradyoxetin, a putative cell density factor of Bradyrhizobium japonicum, and found some inconsistencies in the proposed structure. To elucidate the correct structure, we synthesized model oxetane compounds and confirmed that the NMR data of the synthetic compounds did not match those of the reported bradyoxetin. After reinterpreting the reported NMR data, we concluded that bradyoxetin must be chloramphenicol. Next, some derivatives of 2-hydroxy-4-((methylamino)(phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The overall yield of ent-1b was 26.1% from commercially available (S)-9. The 1 H and 13 C NMR spectra of all synthesized isomers supported their structures well. As mentioned above, none of the NMR data of natural HTI (1) have been reported, so it was impossible to compare the NMR data of natural HTI to the data for the synthesized isomers.…”
Section: Synthesis Of the Four Stereoisomers Of Htimentioning
confidence: 55%
See 2 more Smart Citations
“…The overall yield of ent-1b was 26.1% from commercially available (S)-9. The 1 H and 13 C NMR spectra of all synthesized isomers supported their structures well. As mentioned above, none of the NMR data of natural HTI (1) have been reported, so it was impossible to compare the NMR data of natural HTI to the data for the synthesized isomers.…”
Section: Synthesis Of the Four Stereoisomers Of Htimentioning
confidence: 55%
“…Uncertainty in the structure determination is often observed in the case of compounds for which instrumental analysis data such as NMR are not sufficiently available because they can only be obtained in trace amounts from nature. 12,13) This result may suggest that for the structure determination of the antifungal compound of H. marmoreus, it is necessary to cultivate a large amount of H. marmoreus and then once again attempt to extract the natural products. Although the initial research objective-to determine the structure of the natural product-was not achieved, all synthesized isomers were found to exhibit antifungal activity against the phytopathogenic fungus A. brassicicola.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of two previously reported natural products have been shown to be incorrect by a combination of synthesis of model compounds and computational estimation of NMR chemical shis. 1 Bradyoxetin 1 was reported in 2002 to be a signalling molecule from Bradyrhizobium japonicum but it has now been shown that the compound was chloramphenicol 2 that had been added to the culture medium, presumably to inhibit other microorganisms. HMPC 3 was reported in 2016 to be a quorum-sensing molecule from Ralstonia solanacearum but this structure has been shown to be incorrect and further work is required to deduce the correct structure.…”
mentioning
confidence: 99%